1982
DOI: 10.1111/j.1464-410x.1982.tb13526.x
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Lower Polar Renal Vessel Transposition (the Chapman Procedure) in the Management of Hydronephrosis

Abstract: Over a 15-year period, 19 patients with hydronephrosis due to pelviureteric obstruction associated with lower polar vessels were treated by ureterolysis and transposition of the vessels. Only those patients who, at operation, showed rapid pelvic emptying was not observed, a pyeloplasty was performed in addition. Complete relief of symptoms occurred in 90% of the patients. Post-operative reduction in the degree of hydronephrosis was demonstrated by intravenous urography in 74% and renal pelvic drainage was judg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The UPJO by CV is intermittent and must be suspected in older children with recurrent renal colic pain and hydronephrosis. The renal function may be normal in children with UPJO without Urinary Tract Infection (UTI) (1,10,15,16). In our series, only three children had a major loss of kidney function, probably because of the high delay in the diagnosis (patients with hydronephrosis >4 cm).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The UPJO by CV is intermittent and must be suspected in older children with recurrent renal colic pain and hydronephrosis. The renal function may be normal in children with UPJO without Urinary Tract Infection (UTI) (1,10,15,16). In our series, only three children had a major loss of kidney function, probably because of the high delay in the diagnosis (patients with hydronephrosis >4 cm).…”
Section: Discussionmentioning
confidence: 64%
“…Another important condition is the existence of several anatomic variations as studied by Sampaio (19). These double vascular bundles form a vascular window and could facilitate a UPJ prolapse with increasing obstruction (10). Vascular compression in these cases is not in the UPJ but in the proximal ureter.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al [4], having used a similar approach, reported complete disappearance of symptoms in 90% of the patients with UVH. Viville [7]successfully performed vessel suspension with the Hellström technique in 8 patients with UVH.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, lower segmental vessel transposition was done according to the Hellström technique as modified by Chapman [3, 4]. …”
Section: Methodsmentioning
confidence: 99%